Analisis Faktor-Faktor yang Mempengaruhi Volume Ekspor Ikan Hias (Ornamental Fish) Ke China di PT Indotama Putra Wahana, Kota Bekasi Provinsi Jawa Barat - Siti Ainun; Mauli Kasmi; Mariam Mariam (Journal of Creative Student Research, 2024)
This research aims to understand what factors are significant in the volume of ornamental fish exports to China at PT Indotama Putra Rides located in Bekasi City, West Java Province. Data collection methods used include observation, interviews, and literature study. Meanwhile, the data analysis method applied is quantitative using multiple analysis techniques. Classic assumption tests include linearity test, normality test, autocorrelation test, multicollinearity test, heteroscedasticity test. As well as hypothesis testing, namely the t test (partial test).